The Literacy of Tracking. - Tomaselli, Keyan G.; Grant, Julie (Critical Arts: A South-North Journal of Cultural & Media Studies)
The study examines tracking as literacy, analysed through conventions of storytelling, involving participant observation in the field and through a discussion of cyber-tracking. The conclusion is that the social experience in the post-hunting era is re-created for teaching, memory and nostalgia purposes on the one hand, and is commoditized for tourists on the other.